Inhibition of Murine Leukemia Virus Production in Chronically Infected AKR Cells: A Novel Effect of Interferon - Friedman, Robert M. (1974)
Treatment of AKR cells that had spontaneously become procedures of a murine leukemia virus with a partially purified mouse interferon (> 5 × 10(7) international mouse reference units per mg of protein) inhibited endogenous virus production. This inhibitory effect decreased over a 72-hr period in a manner similar to interferon-induced antiviral activity directed against vesicular stomatitis virus in AKR cells. Despite the inhibitory effect of interferon on infectious murine leukemia virus and viral reverse transcriptase (RNA-dependent DNA polymerase) titers in the culture fluids, intracellular levels of viral groups-specific antigens were significantly increased. These results suggest that interferon treatment in AKR cells inhibited the assembly or release of the virus.